Implementasi PAI dalam Membentuk Karakter Peserta Didik di Era Society - Ernawati, Ernawati; Ramli, Akhmad; Hasan, Muhammad Thoriq Al-Ziyad (Borneo Journal of Islamic Education, 2023)
Abstract The results of the study show that the implementation of PAI in the formation of the character of students can make a positive contribution to the formation of good and noble character. However, it is necessary to take an appropriate and in-depth approach in implementing this program in order to achieve optimal results, how is PAI's contribution in shaping the character of students and its relevance in the era of society, to obtain research data we searched from sources in the form of articles, books and studies that are in accordance with the research objectives, data analysis uses content analysis by understanding the text from the sources obtained, then describes it objectively, systematically, and in detail. Its relevance to the era of society is the use of e-learning multimedia according to the needs of students, so that students are not bored in learning according to the characteristics of millennial students who like content in the form of videos, pictures so that they are more active and understand the material presented easily. in receiving the material delivered with this material little by little affects the character of students, with the hope of developing positive character and minimizing the character of students. Keywords: Implementation of PAI, student character, Society 5.0, Islamic education, technology, learning media. Abstrak Hasil penelitian menunjukkan bahwa implementasi PAI dalam pembentukan karakter peserta didik dapat memberikan kontribusi positif terhadap pembentukan karakter yang baik dan berakhlak mulia. Namun, perlu dilakukan pendekatan yang tepat dan mendalam dalam melaksanakan program ini agar dapat mencapai hasil yang optimal, bagaimana kontribusi PAI dalam membentuk karakter peserta didik dan relevansinya di era society, untuk memperoleh data penelitian kami mencari dari sumber-sumber berupa artikel, buku, dan penelitian-penelitian yang sesuai dengan tujuan penelitian, analisis data menggunakan konten analisis dengan memahami teks dari sumber-sumber yang diperoleh, kemudian menguraikan secara objektif, sistematik, dan terperinci. Relevansinya dengan era society ialah dengan penggunaan multimedia e-learning yang sesuai dengan kebutuhan peserta didik, sehingga peserta didik tidak bosan dalam pembelajaran sesuai dengan karakteristik peserta didik millenial yang menyukai konten-konten berupa video, gambar sehingga mereka lebih aktif dan mudah memahami materi yang disampaikan dalam menerima materi yang disampaikan dengan materi tersebut sedikit demi sedikit mempengaruhi karakter peserta didik, dengan harapan mengembangkan karakter positif dan meminimalisir karakter peserta didik. Kata Kunci: Implementasi PAI, karakter peserta didik, Society 5.0, pendidikan Islam, teknologi, media pembelajaran.